An essential regulator of bacterial division links FtsZ to cell wall synthase activation - Lariviere, Patrick J. (Curr Biol, 2019)
Bacterial growth and division require insertion of new peptidoglycan (PG) into the existing cell wall by PG synthase enzymes. Emerging evidence suggests that many PG synthases require activation to function, however it is unclear how activation of division-specific PG synthases occurs. The FtsZ cytoskeleton has been implicated as a regulator of PG synthesis during division, but the mechanisms through which it acts are unknown. Here we show that FzlA, an FtsZ-binding protein and essential regulator of constriction in Caulobacter crescentus, helps link FtsZ to PG synthesis to promote division. We find that hyperactive mutants of the PG synthases FtsW and FtsI specifically render fzlA, but not other division genes, non-essential. However, FzlA is still required to maintain proper constriction rate and efficiency in a hyperactive PG synthase background. Intriguingly, loss of fzlA in the presence of hyperactivated FtsWI causes cells to rotate about the division plane during constriction and sensitizes cells to cell wall-specific antibiotics. We demonstrate that FzlA-dependent signaling to division-specific PG synthesis is conserved in another α-proteobacterium, Agrobacterium tumefaciens. These data establish that FzlA helps link FtsZ to cell wall remodeling, and is required for signaling to both activate and spatially orient PG synthesis during division. Overall, our findings support the paradigm that activation of SEDS-PBP PG synthases is a broadly conserved requirement for bacterial morphogenesis.